Application of a diagnostic algorithm for the rare deficient variant Mmalton of alpha-1-antitrypsin deficiency: a new approach - Belmonte, Irene; Barrecheguren, Miriam; López-Martínez, Rosa M; Esquinas, Cristina; Rodríguez, Esther; Miravitlles, Marc; Rodríguez-Frias, Francisco (International journal of chronic obstructive pulmonary disease, 2016)
Alpha-1-antitrypsin deficiency (AATD) is associated with a high risk for the development of early-onset emphysema and liver disease. A large majority of subjects with severe AATD carry the ZZ genotype, which can be easily detected. Another rare pathologic variant, the Mmalton allele, causes a deficiency similar to that of the Z variant, but it is not easily recognizable and its detection seems to be underestimated. Therefore, we have included a rapid allele-specific genotyping assay for the detection of the Mmalton variant in the diagnostic algorithm of AATD used in our laboratory. The objective of this study was to test the usefulness of this new algorithm for Mmalton detection. We performed a retrospective revision of all AATD determinations carried out in our laboratory over 2 years using the new diagnostic algorithm. Samples with a phenotype showing one or two M alleles and AAT levels discordant with that phenotype were analyzed using the Mmalton allele-specific genotyping assay. We detected 49 samples with discordant AAT levels; 44 had the MM and five the MS phenotype. In nine of these samples, a single rare Mmalton variant was detected. During the study period, two family screenings were performed and four additional Mmalton variants were identified. The incorporation of the Mmalton allele-specific genotyping assay in the diagnostic algorithm of AATD resulted in a faster and cheaper method to detect this allele and avoided a significant delay in diagnosis when a sequencing assay was required. This methodology can be adapted to other rare variants. Standardized algorithms are required to obtain conclusive data of the real incidence of rare AAT alleles in each region.